The inverse spectral task for a self-adjoint differential operator at a one-dimensional perturbation - Syrovatsky, A.N. (Reports of the National Academy of Sciences of Ukraine, 2014)
The case of a one-dimensional perturbation of the operator of flexon on a finite interval is studied. The inverse task of finding a perturbation by the given spectrum is solved.